TEACHER’S CORRECTIVE FEEDBACK STRATEGIES AND THEIR INFLUENCE ON STUDENTS’ SPEAKING FLUENCY IN EFL CONTEXTS - Merizawati, Henny; Rasyimah, Rasyimah; Sudarso, Hendra; Riztya, Rinda; Wahyudi, Muhammad; Subroto, Desty Endrawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role and effectiveness of corrective feedback in improving students' speaking performance in English as a Foreign Language (EFL) classrooms. Corrective feedback is considered one of the essential strategies in the language learning process, especially in addressing students' language errors both directly and indirectly. Various types of corrective feedback, such as recasts, prompts, and explicit correction, are known to facilitate effective learner uptake and positively impact students' speaking accuracy and fluency. Based on a comprehensive review of academic literature, this study reveals that timely and context-appropriate corrective feedback significantly contributes to the development of students' speaking skills. Additionally, both teachers' and students' perceptions of the importance of corrective feedback play a crucial role in determining its effectiveness. Teachers who can select the appropriate feedback techniques based on students' characteristics and learning situations help learners build confidence and self-correct their language errors more effectively. This study suggests that English teachers should actively and consistently provide corrective feedback during speaking activities. The selection of feedback types and timing should be adjusted to maximize their impact on students' speaking development. Thus, corrective feedback serves not only as a correction tool but also as a pedagogical strategy that encourages students to engage more actively in the language learning process.